2021
DOI: 10.1002/deo2.86
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoscopy in the management of gastroesophageal reflux disease

Abstract: Gastroesophageal reflux disease (GERD) is a common disease that may cause a huge economic burden. Endoscopy is performed not only to rule out other organic diseases but also to diagnose reflux esophagitis or Barrett's esophagus. Non‐erosive GERD (non‐erosive reflux disease [NERD]) is called endoscopy‐negative GERD; however, GERD‐related findings could be obtained through histological assessment, image‐enhanced endoscopy, and new endoscopic modalities in patients with NERD. Moreover, endoscopy is useful to stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 97 publications
(187 reference statements)
0
5
0
Order By: Relevance
“…The American Society of Gastrointestinal Endoscopic Surgery Guidelines recommend the Stretta procedure for patients [21]. However, another study reported different results [22], and the Stretta method needs to be re-examined [23]. Higuchi et al introduced the Stretta method in Japan in 2006 and reported its results [24]; however, it is not currently covered by medical insurance in Japan.…”
Section: Various Endoscopic Treatments For Gerdmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Society of Gastrointestinal Endoscopic Surgery Guidelines recommend the Stretta procedure for patients [21]. However, another study reported different results [22], and the Stretta method needs to be re-examined [23]. Higuchi et al introduced the Stretta method in Japan in 2006 and reported its results [24]; however, it is not currently covered by medical insurance in Japan.…”
Section: Various Endoscopic Treatments For Gerdmentioning
confidence: 99%
“…Higuchi et al introduced the Stretta method in Japan in 2006 and reported its results [24]; however, it is not currently covered by medical insurance in Japan. Methods for injecting bulking agents have not been used recently because of safety issues [23, 25].…”
Section: Various Endoscopic Treatments For Gerdmentioning
confidence: 99%
“…45 Other endoscopic anti-reflux therapies 1) Anti-reflux mucosectomy Anti-reflux mucosectomy (ARMS) was initially introduced by Inoue et al 56 in patients with short-segment BE with high-grade -B). 57 ARMS helps create mucosal defects in approximately 2/3 to 4/5 of the circumference on the lesser curvature of the cardiac mucosa, leading to scarring and, consequently, narrowing of the EGJ opening. ARMS-C was shown to be effective and safe for GERD treatment at 6 months; 63% of the patients discontinued PPI, while 30% of the patients reduced their PPI intake.…”
Section: Endoscopic Full-thickness Suturingmentioning
confidence: 99%
“…Endoscopic approaches, such as radiofrequency ablation, endoscopic fundoplication, and endoscopic mucosal resection, have been developed for GERD management. These methods, notably endoscopic full-thickness plication (EFTP), are recognized for their effectiveness in symptom reduction and safety, often presenting fewer complications compared to surgical options 14 15 . Short-term outcomes post-procedure, such as immediate symptom relief and reduced medication dependency, are generally positive 15 .…”
Section: Introductionmentioning
confidence: 99%
“…EFTP represents a significant advance in minimally invasive GERD management. The technique involves creating a functional anti-reflux valve by applying transmural sutures at the gastroesophageal junction, folding and connecting gastric fundus segments to the esophagus, ultimately enhancing the valvular mechanism and reducing gastroesophageal reflux 14 15 16 . The long-term effectiveness and safety of EFTP have been supported by several randomized controlled trials (RCTs) and prospective studies 17 18 19 20 .…”
Section: Introductionmentioning
confidence: 99%